Service delivery for microsystems production: A study - Durugbo, Christopher; Tiwari, Ashutosh; Alcock, Jeffrey R. (Elsevier, 2012)
This paper presents the findings of an investigation into the industry practice of service delivery within microsystems technologies (MST) (also known as micro- electro-mechanical systems, MEMS) production. A study was undertaken to evaluate 100 MST companies that deliver integrated products and services i.e. a product- service system (PSS). The aim of the study is to: (i) analyse the main types of services delivered by MST companies, and (ii) make recommendations for improving MST production. The PSS approach to production and manufacturing is introduced and used to evaluate the current state of service delivery within MST production. The findings of the study are then used to make recommendations for improving future MST production.
Keywords: Microsystems technology; Micro-electro-mechanical systems; Production management; Product-service systems; Value creation; Service; Business model